The indigenous & the foreign - The Jesuit Presence in 17th Century Ethiopia - Boavida, Isabel (2012)
In the rural plateaux of northern Ethiopia, one can still find scattered ruins of monumental buildings alien to the country's ancient architectural tradition. This little-known and rarely studied architectural heritage bears silent witness to a fascinating if equivocal cultural encounter that took place in the 16th-17th centuries between Orthodox Ethiopians and Catholic Europeans. The Indigenous and the Foreign explores the enduring impact of the encounter on the religious, political and artistic life of Christian Ethiopia, one not readily acknowledged, not least because the public conversion of the early 17th-century King Susenyos to Catholicism resulted in a bloody civil war enveloped in religious intolerance.